PENGGUNAAN MEDIA BUSY BOOK UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA DINI KELOMPOK A - Dina Andriani Dewi Anggarini; Medi Yana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the use of busy book media in improving the cognitive abilities of early childhood students in Group A at RA Bustanul Ulum Pakong, Pamekasan. A descriptive qualitative approach was employed, involving teachers and children aged 4–5 years (n=20 children and 2 teachers) as subjects. Data were collected through observation, interviews, and documentation. Data analysis included data reduction, presentation, and conclusion drawing, while validity was ensured through source and technique triangulation. The results showed that the implementation of busy book media was carried out through three stages: planning, implementation, and evaluation. The use of busy book media improved children's cognitive abilities, particularly in recognizing colors, shapes, numbers, and simple patterns. Additionally, this media enhanced children's concentration, memory, logical thinking skills, and active participation during learning. Supporting factors included attractive media design, interactive activities, teacher assistance, and a conducive learning environment. Inhibiting factors consisted of differences in children's abilities, limited availability of media, and limited learning time. Therefore, busy book media can be considered an effective, interactive, and enjoyable learning medium to support the cognitive development of early childhood learners.